P-217 Feasibility of a Mobile Personalized Learning System for Assessing Daily IBD Symptoms and Quality of Life. (March 2016) - Adler, Jeremy; Saeed, Shehzad; Thakkar, Sunny; Eslick, Ian; Margolis, Peter; Provost, Lloyd; Kaplan, Heather
Abstract : Background: Assessment of Inflammatory bowel disease (IBD) is complicated by day-to-day variation in symptoms. Management is further challenged by incomplete symptom recall and lack of data about how patients are feeling between visits. We designed a personalized learning system (PLS) to allow patients to work with their providers to track symptoms between visits and learn about what improves their symptoms. Methods: We recruited pediatric patients with IBD to pilot-test the PLS system. Inclusion required active symptoms that the patient felt were attributable to their IBD, and having a mobile phone capable of text messaging. Patients self-identified customized symptoms most relevant to their experience and also collected standard Patient Reported Outcome Measurement Information System (PROMIS). Daily text messages prompted patients to respond rating symptom levels. Weekly PROMIS measures were assessed via text link to online survey. Patients could also submit journal text entries at any time. We assessed feasibility of monitoring patients remotely and patient perception of these methods. The duration of the study was determined by joint decision of patient and provider based on goal attainment. Data were graphed in real-time and immediately available for providers and patients. Patients were dropped from study if non-responsive ≥60 days. Results: Twenty-eight patients enrolled in the study, but 5 withdrew or were lost to follow-up before starting data collection. Twenty-three patients collected data over a total of 167 patient-months. In aggregate, 226 symptoms were tracked (average 9.8 per patient). The most frequent symptoms selected for tracking by patients included: Daily stools (n = 14); abdominal pain (n = 14); bloody stools (n = 7); stool consistency (n = 5); sleep duration (n = 5); nausea (n = 5); and nocturnal stools (n = 5). By 60 days, 87% remained in the study (3 completed the study). By 90 days, 78% remained in the study (1 additional completion, 1 dropped for non-response). By 5 months, 7 completed the study and 3 dropped out (Figure 1). Question adherence varied by symptom. Among those completing the study, the most frequently answered were sleep duration (96%), stool consistency (92%), daily stools (81%), and abdominal pain (64%). Response to weekly surveys was poor (24%–35%). Overall adherence among actively participating patients was 72% (range 28 to 95%). Journal entries were submitted by 14 of 23 (61%) patients (range 1–182, median 10 per patient). Exit surveys revealed following patient learnings: 64% "learned something about" their IBD; 79% felt PLS changed how GI visits went; 43% changed how they think about IBD; 50% felt PLS allowed them to better manage their IBD, and 71% felt they could keep fatigue from interfering with activities. Conclusions: For pediatric IBD patients with active symptoms, daily symptom tracking via text message is feasible for at least 90 days. Weekly text message links to web surveys are not effective. Patients felt they learned something about their IBD and that the data changed how they met with their GI doctors and may have helped with some aspects of symptom management. Tracking symptoms via daily text messaging may benefit IBD patients with active symptoms. This supports conducting N-of-1 studies to target symptom improvement.